Students’ Perception and Utilization of Reprographic Section in Federal University of Petroleum Resources, Library - Sambo, Atanda Saliu; Aghojare, Blessing; Ejitagha, Stella (MiddleBelt Journal of Library and Information Science, 2016)
The impact of reprographic on document delivery service in libraries and information centres cannot be deserted. This paper assessed the students’ perception and utilization of reprographic services in Federal University of Petroleum Resources, Library. The study population comprises 2,213 students of the university. The instrument used for data collection was questionnaire. Research questions were answered using frequency, bar chart and percentages for easy interpretation. The major findings of the study revealed that reprographic section was not only affected by lack of spares and consumable materials but also lack of technical know-how, insufficient equipment, funds and lack of air-condition/space among others. The frequent use of this section indicated that a lot need to be done to enhance and expand services of the unit, since some services like book binding, thesis binding, thermal binding, photograph, microfilm/micro reader, xerography and drilling were not done. The study recommends expansion of the unit, more funds and experts should be involved in the unit so as to curb the problems of technical knowhow and spares/consumables.